The association between Parkinson’s disease and autoimmune diseases: A systematic review and meta-analysis - Li, Mingqiang; Wan, Juan; Xu, Zhenhong; Tang, Beisha (Frontiers in Immunology, 2023)
Parkinson's disease (PD) is a neurodegenerative disorder that frequently occurs in the older population. Previous epidemiological studies have suggested an association between PD and autoimmune diseases (AIDs). However, some studies have shown conflicting results. This study aimed to summarize existing epidemiological studies on the association between PD with AIDs and to conduct a meta-analysis of combinable results. Four electronic databases (PubMed, Embase, Web of Science Core Collection, and MEDLINE) were searched from each database’s inception date until December 12, 2022. All studies that explored the relationship between PD and AIDs were included for quantitative analysis and qualitative review. The pooled relative risk with 95% confidence intervals (CIs) was calculated using a random or fixed effects model. A total of 46 observational studies involving 873,643 patients and 13,402,821 controls were included; ultimately, 38 studies were included in the meta-analysis. The risk of PD combined with AIDs was significantly higher (odds ratio [OR]=1.55, 95% CI: 1.33–1.81), and subgroup analysis found no significant differences in risk by study type, gender, age, and race. Regarding the AID types, the results showed an increased risk of PD combined with bullous pemphigoid (OR=2.67, 95% CI: 2.15–3.31), inflammatory bowel disease (OR=1.30, 95% CI: 1.18–1.45), Crohn’s disease (OR=1.30, 95% CI: 1.20–1.42), ulcerative colitis (OR=1.31, 95% CI: 1.14–1.50), Sjögren's syndrome (OR=1.61, 95% CI: 1.24–2.09), and Graves’ disease (OR=1.45, 95% CI: 1.24–1.70) than controls. However, there appeared to be no significant association between PD and systemic lupus erythematosus (OR=0.82, 95% CI: 0.66–1.03), multiple sclerosis (OR=2.02, 95% CI: 0.87–4.70), rheumatoid arthritis (OR=0.79, 95% CI: 0.61–1.03), or celiac disease (OR=1.16, 95% CI: 0.79–1.69). This study supports the existence of a strong link between AIDs and PD. When PD and AIDs are identified, clinicians need to be aware of the possibility of coexistence. However, there are some limitations of this study, such as the apparent heterogeneity of some of the results and the fact that most of the included study types were retrospective. Therefore, future larger prospective cohort studies are needed to further explore the interaction between PD and AIDs.